Síndrome de ativação macrofágica em paciente com Lúpus eritematoso sistêmico juvenil - de Carvalho, Simone Manso [UNESP]; Silva, João Henrique do Amaral [UNESP]; Sato, Juliana de Oliveira [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Magalhães, Claudia Saad [UNESP] (My University, 2008)
Reactive haemophagocytosis or macrophage activation syndrome (MAS) is a complication of systemic inflammatory disorders, caused by expansion of T cells and haemophagocytic macrophages, with cytokine overproduction. It has been described most often in systemic juvenile idiopathic arthritis and rarely in juvenile systemic lupus erythematosus (JSLE). Objective: To report a JSLE case who developed MAS in association with spleen infarct triggered by infection, with fatal outcome. Case report: A 7-year old-girl diagnosed with lupus since age 5-y developed several episodes of arthritis flare, cytopenias, severe alopecia, headaches and recurrent episodes of respiratory infections with intermittently increased serum transaminases. Anti-DNA and anti-cardiolipin IgG and IgM were identified and Class III lupus glomerulonephritis was diagnosed by renal biopsy. The patient was treated with methylprednisolone pulses, prednisone, azatioprine and hydroxychloroquine. Last admitted due to pneumonia, she evolved into abdominal crisis and seizures, undergoing splenectomy and evolving into haemorragic shock with fatal outcome. A spleen infarct was found and anti-CD163 antibodies staining disclosed intense haemophagocytic macrophage infiltration. Conclusion: This outcome suggests infection-triggered MAS overlapping lupus flare with persistent fever, cytopenia, liver dysfunction, hepatomegaly and splenomegaly as cytokine excess driven effect. Anti-cardiolipin antibodies may also had a coagulopathy precipiting role.
Macrophage activation syndrome in a patient with juvenile systemic lupus erythematosus
Keywords: Haemophagocytosis; Infections; Juvenile systemic lupus erythematosus; Macrophage activation syndrome